ASSESSING THE IMPACT OF REMITTANCES FROM INDONESIAN MIGRANT WORKERS ON HOUSEHOLD WELFARE: INSIGHTS FROM THE SHARIA ECONOMIC FRAMEWORK - Agus Salim; Moh. Bahrudin; Erike Anggraeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study is grounded in the philosophy of maqāṣid al-sharī‘ah in Islamic economics, which positions welfare as the ultimate goal of the Shariah through the protection of religion, life, intellect, lineage, and wealth. The phenomenon of remittances sent by Indonesian Migrant Workers (PMI) has become a particular concern in East Lampung Regency, a region heavily dependent on remittances as a significant economic driver. The uniqueness of the problem arises when remittances not only affect economic aspects but also influence social, spiritual, and family dynamics, including religious practices, gender roles, and household stability. This research aims to analyze the implementation and utilization of PMI remittances and their impact on family welfare based on maqāṣid al-sharī‘ah indicators. A qualitative descriptive approach was employed through field studies using observation, documentation, and in-depth interviews with PMI and families receiving remittances in East Lampung Regency. The findings indicate that remittances contribute to improving family welfare, particularly in fulfilling basic needs, education, health, and strengthening family spirituality. However, negative effects were also identified, such as consumptive use of remittances, economic dependency, rising divorce cases due to long-distance separation and weak communication, and the absence of parental roles that may threaten family resilience. The perspective of maqāṣid al-sharī‘ah serves as an essential analytical tool to assess the balance between the benefits and risks of remittances holistically.